Connected Through Mediated Social Touch: “Better Than a Like on Facebook.” A Longitudinal Explorative Field Study Among Geographically Separated Romantic Couples - van Hattum, Martijn T.; Huisman, Gijs; Toet, Alexander; van Erp, Jan B. F. (Frontiers in Psychology, 2022)
In recent years, there has been a significant increase in research on mediated communication via social touch. Previous studies indicated that mediated social touch (MST) can induce similar positive outcomes to interpersonal touch. However, studies investigating the user experience of MST technology predominantly involve brief experiments that are performed in well-controlled laboratory conditions. Hence, it is still unknown how MST affects the relationship and communication between physically separated partners in a romantic relationship, in a naturalistic setting and over a longer period of time. In a longitudinal explorative field study, the effects of MST on social connectedness and longing for touch among geographically separated romantic couples were investigated in a naturalistic setting. For two weeks, 17 couples used haptic bracelets, that were connected via the internet, to exchange mediated squeeze-like touch signals. Before and after this period, they reported their feelings of social connectedness and longing for touch through questionnaires. The results show that the use of haptic bracelets 1) enhanced social connectedness among geographically separated couples but 2) did not affect their longing for touch. Interviews conducted at the end of the study were analyzed following the thematic analysis method to generate prominent themes and patterns in using MST technology among participant couples. Two main themes were generated that captured (a) the way the bracelets fostered a positive one-to-one connection between partners and (b) the way in which participants worked around their frustrations with the bracelets. Detailed findings and limitations of this longitudinal field study are further discussed, and suggestions are made for future research.